2019
DOI: 10.3133/fs20183081
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the pulse of our Nation's rivers and streams—The U.S. Geological Survey streamgaging network

Abstract: In the late 1800s, John Wesley Powell, second Director of the U.S. Geological Survey (USGS), proposed gaging the flow of rivers and streams in the Western United States to evaluate the potential for irrigation. Around the same time, several cities in the Eastern United States established primitive streamgages to help design water-supply systems. Streamgaging technology has greatly advanced since the 1800s, and USGS hydrographers have made at least one streamflow measurement at more than 37,000 sites throughout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…2, 3). This is important given that the USGS operates thousands of streamgages nationwide (Eberts et al 2018). Positive kokanee and yellow perch DNA detections even occurred at sites where these species are at such low abundances that they are not captured by resource managers in annual population surveys.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2, 3). This is important given that the USGS operates thousands of streamgages nationwide (Eberts et al 2018). Positive kokanee and yellow perch DNA detections even occurred at sites where these species are at such low abundances that they are not captured by resource managers in annual population surveys.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study from southwest Idaho demonstrated that eDNA samples collected monthly at streamgages in a large river basin can provide meaningful information about the distribution of both common and rare fishes, especially when combined with the discharge and temperature data typically collected at gages (Pilliod et al, in press). This is important given that the USGS operates thousands of streamgages nationwide (Eberts et al 2018). The cost-benefit ratio of adding eDNA biosurveillance to routine USGS hydrologic monitoring activity was low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The U.S. Geological Survey (USGS) operates one of the largest streamflow information networks in the world, collecting water-level data at over 10,000 stations. In 2018, over 8200 of these stations continuously monitored streamflow (i.e., discharge) year-round and disseminated the data online [1]. USGS streamflow information is queried frequently by various agencies and the general public and is used for a broad range of purposes including flood hazard warning, water resource management, and recreation.…”
Section: Introductionmentioning
confidence: 99%
“…USGS streamflow information is queried frequently by various agencies and the general public and is used for a broad range of purposes including flood hazard warning, water resource management, and recreation. Streamflow measurement stations (gaging stations) rely upon periodic measurements made by hydrographers, with an estimated 80,000 on-site streamflow measurements collected each year to develop rating curves that relate water level to discharge [1]. Developing remotely sensed approaches to on-site streamflow measurement could reduce or eliminate risk to hydrographers during extreme events, augment and economize current streamflow information networks, and facilitate expansion of networks into ungaged basins, including remote watersheds that are difficult to access.…”
Section: Introductionmentioning
confidence: 99%